Learning theory and online technology - Harasim, Linda M. (Routledge, 2012)
"Learning Theory and Online Technology offers a powerful overview of the current state of e-learning, a foundation of its historical roots and growth, and a framework for distinguishing among the major approaches to e-learning. It effectively addresses pedagogy (how to design an effective online environment for learning), evaluation (how to know that students are learning), and history (how past research can guide successful online teaching and learning outcomes). An ideal textbook for Educational Technology Masters, PhD, and Certificate programs, readers will find Learning Theory and Online Technology provides a synthesis of the key advances in e-learning theory, the key frameworks of research, and clearly links theory and research to successful learning practice"-- Provided by publisher.